2019
DOI: 10.3390/ijms20051134
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Resveratrol Supplementation Prevents Cognitive Decline in Senescent Mice Offspring

Abstract: A variety of environmental factors contribute significantly to age-related cognitive decline and memory impairment in Alzheimer’s Disease (AD) and other neurodegenerative diseases. Nutrition can alter epigenetics, improving health outcomes, which can be transmitted across generations; this process is called epigenetic inheritance. We investigate the beneficial effects of maternal resveratrol supplementation in the direct exposed F1 generation and the transgenerational F2 generation. The offspring was generated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 66 publications
0
30
0
Order By: Relevance
“…Resveratrol activates a transcriptional coactivator, PGC-1α, that promotes energy metabolism by glucose uptake and mitochondrial biogenesis (Lagouge et al, 2006;Kumar and Lombard, 2015;Parihar et al, 2015). Recent studies have demonstrated that maternal resveratrol supplementation and vitamin D combined with resveratrol could prevent cognitive impairment in SAMP8 mice offspring through amyloidogenic pathways, neuroinflammation, tau phosphorylation, epigenetic changes, and cell signaling pathways (Cheng et al, 2017;Izquierdo et al, 2019). Another study indicated the ameliorative action of resveratrol in hippocampal neurodegeneration and memory performance (Gomes et al, 2018).…”
Section: Resveratrolmentioning
confidence: 99%
“…Resveratrol activates a transcriptional coactivator, PGC-1α, that promotes energy metabolism by glucose uptake and mitochondrial biogenesis (Lagouge et al, 2006;Kumar and Lombard, 2015;Parihar et al, 2015). Recent studies have demonstrated that maternal resveratrol supplementation and vitamin D combined with resveratrol could prevent cognitive impairment in SAMP8 mice offspring through amyloidogenic pathways, neuroinflammation, tau phosphorylation, epigenetic changes, and cell signaling pathways (Cheng et al, 2017;Izquierdo et al, 2019). Another study indicated the ameliorative action of resveratrol in hippocampal neurodegeneration and memory performance (Gomes et al, 2018).…”
Section: Resveratrolmentioning
confidence: 99%
“…The influence of maternal resveratrol supplementation on progeny has also been discovered recently. It has been shown that maternal resveratrol therapy can prevent cognitive decline in senescent mice progeny [52]. Tanaka et al recently reported that prenatal resveratrol administration during lactation could decrease liver fatty acid synthesis of adult male rat progeny [53].…”
Section: Discussionmentioning
confidence: 99%
“…The supplementation of folic acid, a methyl donor, improves cognitive functions in participants who tend to decline with age (165). Interestingly, maternal supplementation of resveratrol promotes cognitive decline in the SAMP8 mice offspring via increasing global methylation levels and decreasing hydroxymethylation levels (166). Consequently, the DNA methyltransferase or the methyl donor may be potential treatments for patients with AD.…”
Section: Epigenetic Therapeutic Strategies For Admentioning
confidence: 99%